Implementasi Media Pembelajaran E-Flipbook Pada Materi Vektor Kelas X SMK - Ruanda, Rizky; Susanto, Hari Purnomo; Qudsiyah, Khoirul (Program Studi Pendidikan matematika STKIP PGRI Pacitan STKIP PGRI Pacitan, 2025)
This study aims to explore and analyze the implementation of e-flipbook learning media on vector material in 10th-grade students at SMK Negeri 1 Pacitan. The research method used is qualitative with a case study approach. Data were collected through observation, interviews, and documentation. The findings indicate that the use of e-flipbook as a learning medium can enhance students' understanding of vector concepts, motivate them in the learning process, and provide variety in teaching methods that are more interactive and engaging. However, there are some technical challenges that need to be addressed, such as limited access to technology and the digital media skills of teachers and students. Overall, the implementation of e-flipbook has great potential to support an effective and efficient learning process.